The Associations among Insulin Resistance, Hyperglycemia, Physical Performance, Diabetes Mellitus, and Cognitive Function in Relatively Healthy Older Adults with Subtle Cognitive Dysfunction - Umegaki, Hiroyuki; Makino, Taeko; Uemura, Kazuki; Shimada, Hiroyuki; Hayashi, Takahiro; Cheng, Xian Wu; Kuzuya, Masafumi (Frontiers in Aging Neuroscience, 2017)
Insulin resistance (IR), diabetes mellitus (DM), sarcopenia, and cognitive dysfunction are thought to be mutually associated. We conducted a comprehensive assessment of the relationships among IR, gait speed, hyperglycemia, and DM by cross-sectionally analyzing the baseline data of an interventional study for cognitive preservation with physical exercise (the TOyota Preventional Intervention for Cognitive decline and Sarcopenia [TOPICS]). The participants (n=444) were relatively healthy older individuals who had mild cognitive impairment without dementia, and 61 of the participants had DM. Slow gait speed and hyperglycemia were associated with cognitive dysfunction, mainly in the executive function domain, whereas IR was associated with memory impairment. The participants with DM had lower general cognition and executive function. Executive dysfunction in the DM participants seemed to be partly explained by hyperglycemia and/or slow gait speed. Our findings confirmed that IR, DM, sarcopenia, and cognitive dysfunction are mutually associated in complex ways. Understanding the mechanisms underlying these associations will lead to effective strategies to prevent and treat cognitive dysfunction in older individuals.